Justifikasi Ilmiah Dalam Pembangunan Kawasan Permukiman Sebagai Refleksi Filsafat Ilmu Atas Model, Rasionalitas, Dan Realitas Sosial Pada Pembangunan Kawasan Kahayan Riverside: Scientific Justification In Residential Area Development As A Philosophy Of Science Reflection On Models, Rationality, And Social Reality In The Development Of The Kahayan Riverside Area - Adhi Muhtadi; Hendri Tuah; Enny Mamenda Veronica; Rury Rianson Digut; Suprayitno Suprayitno; Sonianto Sonianto (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The development of residential areas represents a form of applied scientific practice that extends beyond technical implementation to include claims of rationality and scientific justification. In practice, development decisions are commonly grounded in the use of models, standards, and regulations that are treated as objective representations of reality and legitimate bases for intervention. However, such applications of scientific knowledge often encounter complex and dynamic social realities, raising questions about the limits of scientific objectivity and rationality. This article aims to reflect on the role of scientific justification in residential area development from the perspective of philosophy of science. The study employs a qualitative approach using conceptual and reflective analysis of philosophical literature, development standards and policies, and the case study of the Kahayan Riverside area. The findings indicate that scientific models and standards function not only as technical analytical tools but also as mechanisms of epistemic legitimacy that justify development practices. Contemporary philosophy of science reveals that models are perspectival, rationality is contextual, and social reality is integral to scientific practice. Therefore, residential area development should be understood as a socially embedded practice that requires critical reflection on its scientific justifications.